2021
DOI: 10.1101/2021.08.24.457187
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiling Transcription Initiation in Peripheral Leukocytes Reveals Severity-Associated Cis-Regulatory Elements in Critical COVID-19

Abstract: The contribution of transcription factors (TFs) and gene regulatory programs in the immune response to COVID-19 and their relationship to disease outcome is not fully understood. Analysis of genome-wide changes in transcription at both promoter-proximal and distal cis-regulatory DNA elements, collectively termed the 'active cistrome,' offers an unbiased assessment of TF activity identifying key pathways regulated in homeostasis or disease. Here, we profiled the active cistrome from peripheral leukocytes of cri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…19 Lam et al stratified patients by measuring lung injury with a modified Murray score that assigns a score between 0 and 4 based on five criteria. 20 Lee et al used NEWS standard to stratify the disease status and found that type I interferons (IFNs) exacerbate inflammation in severe infections. 9 Since the classification systems from the WHO and NHCC have similar guidelines, we expect the results to be comparable between similar infection severities.…”
Section: Covid-19 Infection Severitymentioning
confidence: 99%
“…19 Lam et al stratified patients by measuring lung injury with a modified Murray score that assigns a score between 0 and 4 based on five criteria. 20 Lee et al used NEWS standard to stratify the disease status and found that type I interferons (IFNs) exacerbate inflammation in severe infections. 9 Since the classification systems from the WHO and NHCC have similar guidelines, we expect the results to be comparable between similar infection severities.…”
Section: Covid-19 Infection Severitymentioning
confidence: 99%
“…For this purpose, we performed global TF activity profiling using the bulk RNA-seq dataset, which was collected in parallel with ATAC-seq data to identify TFs with significantly regulated gene module scores across our experimental groups. SARS-CoV-2 infection of Calu-3 cells induced activity of the inflammatory TF families (STATs, IRFs, and NFκB-1) ( Fig 6A ), whose signalling is associated with severe COVID-19 cases [ 63 ]. JQ-1 treatment in the presence of SARS-CoV-2 infection suppressed the activity of these inflammatory TF families, suggesting an anti-inflammatory effect of JQ-1 ( Fig 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 infection of Calu-3 cells induced activity of the inflammatory TF families (STATs, IRFs, and NFκB-1) (Fig. 6A), whose signalling is associated with severe COVID-19 cases (Lam et al, 2021). JQ-1 treatment in the presence of SARS-CoV-2 infection suppressed the activity of these inflammatory TF families, suggesting an anti-inflammatory effect of JQ-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Irrespective of the infection status, JQ-1 treatment suppressed activity of the TF families that regulate cell cycle and proliferation (E2F & MYB), whose synergistic signalling is associated with severe lung injury in COVID-19 cases (Lam et al, 2021). This is in line with JQ-1-mediated dysregulation of cell cycle-regulating genes (Fig.…”
Section: Resultsmentioning
confidence: 99%